2008
DOI: 10.1021/bi800299u
|View full text |Cite
|
Sign up to set email alerts
|

Transition State Chirality and Role of the Vicinal Hydroxyl in the Ribosomal Peptidyl Transferase Reaction

Abstract: The ribosomal peptidyl transferase is a biologically essential catalyst responsible for protein synthesis. The reaction is expected to proceed through a transition state approaching tetrahedral geometry with a specific chirality. To establish that stereospecificity, we synthesized two diastereomers of a transition state inhibitor with mimics for each of the four ligands around the reactive chiral center. Preferential binding of the inhibitor that mimics a transition state with S chirality establishes the spati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
17
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 43 publications
4
17
0
Order By: Relevance
“…It is important to note that the ribosome does not provide groups that act as general acids or bases 2,[21][22][23] . The proton shuttles as depicted result in the protonation of the carbonyl oxygen before the less favourable protonation of the leaving 39-oxygen, following previous proposals 24,25 . The catalysis of peptide bond formation on the ribosome, compared with a spontaneous model reaction in solution, is entirely due to a change of the activation entropy, DS { (ref.…”
Section: Research Lettersupporting
confidence: 70%
“…It is important to note that the ribosome does not provide groups that act as general acids or bases 2,[21][22][23] . The proton shuttles as depicted result in the protonation of the carbonyl oxygen before the less favourable protonation of the leaving 39-oxygen, following previous proposals 24,25 . The catalysis of peptide bond formation on the ribosome, compared with a spontaneous model reaction in solution, is entirely due to a change of the activation entropy, DS { (ref.…”
Section: Research Lettersupporting
confidence: 70%
“…Because of the proximity of the O2’ hydroxyl to the O3’ atom of A76 that is linked to the peptide chain, it was proposed that O2’ hydroxyl is critical for proton shuttling from the attacking α-amino group to the leaving O3’ hydroxyl. Indeed, it has been shown that the O2’ hydroxyl group remains neutral in the transition state confirming its role in the proton shuttle [73]. More recently, Strobel and colleagues have concluded that at the transition state the α-amino nucleophile is neutral, which is in a stark contrast to the development of the positively charged amino nucleophile during an uncatalyzed aminolysis reaction in solution [74].…”
Section: Catalytic Mechanismmentioning
confidence: 99%
“…This is important, as the 2 ¢ OH group can receive a proton only if it simultaneously donates a proton to some other group. However, model studies suggested that the carbonyl oxygen of the pept-tRNA, rather than the 3 ¢ OH, accepts the proton from the 2 ¢ OH (Huang et al 2008 ;Rangelov et al 2006 ) . Such a shuttle mechanism may be six-membered, with two protons simultaneously changing their positions in the TS, or eight-membered with three protons "in fl ight" in the TS; the latter TS includes a water molecule which is found in the right position in the crystal structures of the 50S subunits in the complex with TS analogs (Schmeing et al 2005a ;Wallin and Aqvist 2010 ) .…”
Section: Peptide Bond Formationmentioning
confidence: 99%